Long-term persistence of antibodies after diphtheria/tetanus vaccination in immunosuppressed patients with inflammatory rheumatic diseases and healthy controls. Issue 33 (5th August 2022) - Mischlinger, Johannes; Jaeger, Veronika K.; Ciurea, Adrian; Gabay, Cem; Hasler, Paul; Mueller, Ruediger B.; Siegrist, Claire Ann; Villiger, Peter; Walker, Ulrich A.; Hatz, Christoph; Bühler, Silja
Abstract: Many vaccines demonstrate high effectiveness for years. This prospective multicentre study was conducted in Switzerland to assess the long-term persistence of antibodies to the diphtheria/tetanus (dT)-vaccine in adult patients with rheumatic diseases (PRDs). 163 PRDs and 169 controls were included in the study. The median age of all participants was 50 years (range: 18–83 years) and 56% were female. After a median time interval of 16 years after vaccination, the median anti-vaccine antibody concentrations were lower in PRDs than in controls for tetanus (1.68 vs 2.01; p = 0.049) and diphtheria (0.05 vs 0.22; p = 0.002). Based on the currently accepted seroprotection threshold (antibody concentration ≥ 0.1 IU/ml), PRDs had lower proportions of short-term tetanus and diphtheria protection as demonstrated by crude odds ratios (OR) of 0.30 (p = 0.017) and OR: 0.52 (p = 0.004), respectively. After adjusting for 'age' and 'time since last dT vaccination', the strength of associations became weaker; for tetanus, borderline evidence remained for a true difference between PRDs and controls (OR: 0.36 [p = 0.098]), however, not for diphtheria (OR: 0.86 [p = 0.58]). We hypothesize that in the presence of rheumatic diseases and its immunosuppressive treatment, vaccine-specific long-lived plasma cells (LLPCs) may be diminished or competitively displaced by rheumatism-specific LLPCs, a process which may decrease the persistence of vaccine-specific antibodies. Novel studies should be designed by incorporating methodologies allowing to determine the attributable fraction of immunosuppressive/immunomodulatory medications and rheumatic disease itself on long-lasting vaccine-specific antibody persistence, as well as, further study the role of LLPCs.